Virtual reality as a possible aged care technology – opportunities and prejudices from older persons and their caregivers in a qualitative study - Felber, Nadine Andrea; Mihailov, Emilian; Wangmo, Tenzin (Frontiers in Virtual Reality, 2025)
IntroductionVirtual Reality (VR) offers new opportunities in healthcare, especially for older adults, who often suffer from reduced mobility, cognitive decline and reduced social contact. However, VR is still not widely accepted among current older generations and their caregivers as a healthcare tool.MethodsThis qualitative study explores the perceptions of older adults and their caregivers, formal and informal, on VR and its potential use in aged care. 67 interview participants explained their views after being presented with a video showing older adults using immersive VR technology. The data was analyzed using thematic analysis.ResultsThe study reveals that the three stakeholder groups foresee potential of VR as an entertaining and therapeutic technology, but that they also worry about VRs’ impact on loneliness, the cognitive capabilities needed to use it, as well as its safety for older adults.DiscussionOur study identifies clear opportunities for VR technology in aged care. Comparing our results to current research on VR and older persons, our research points to important prejudices that need to be dismantled before VR will be widely adopted as a technology in aged care for current older persons.